2002
DOI: 10.1002/bip.10088
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐IR microspectroscopic imaging of breast tumor tissue sections

Abstract: IR microspectroscopic imaging is a relatively new approach for the examination of tissue sections. In contrast to standard light microscopy based procedures, the IR approach requires neither sample staining nor fixation. The IR spectra of breast tumor tissue sections are obtained via a microscope equipped with a focal plane array detector. This enabled the simultaneous collection of individual mid-IR spectra from thousands of different sample positions with a spatial resolution near the diffraction limit. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 11 publications
(15 reference statements)
0
30
0
Order By: Relevance
“…2 shows the absorption spectra of normal (curve I), benign (curve II) and malignant (curve III) tissues in 1400-1750 cm À1 region. The peak at 1655 cm À1 (corresponding to amide I bond), which can be ascribed to the absorption of the CQO stretching vibration coupled to the in-phase bending of the N-H bond [8], and the peak at 1543 cm À1 (corresponding to amide II bond) are stronger in malignant tissue but weaker in normal and benign tissues. Then, the absorption peak at 1500 cm À1 can be observed only in malignant tissue and might result from the CQC vibration of pyrrole.…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the absorption spectra of normal (curve I), benign (curve II) and malignant (curve III) tissues in 1400-1750 cm À1 region. The peak at 1655 cm À1 (corresponding to amide I bond), which can be ascribed to the absorption of the CQO stretching vibration coupled to the in-phase bending of the N-H bond [8], and the peak at 1543 cm À1 (corresponding to amide II bond) are stronger in malignant tissue but weaker in normal and benign tissues. Then, the absorption peak at 1500 cm À1 can be observed only in malignant tissue and might result from the CQC vibration of pyrrole.…”
Section: Resultsmentioning
confidence: 99%
“…This spatial resolution was long believed to be the best possible, and led to promising initial results in IR imaging and breast cancer research [2][3][4][5][6][7] , but can make it difficult or impossible to distinguish certain cell types in breast tissue, limiting the usefulness of the technique for histopathology. Recent work with 2.7 μm image pixels 8 hinted at the advantage of increased definition in IR imaging, but pixel binning and low NA prevented adequate sampling 9 and the full utilization of the increased magnification.…”
Section: Hd Ft-irmentioning
confidence: 99%
“…Imaging and point-mapping approaches were compared in the recent analysis of a sample of breast tissue demonstrating adverse pathologic conditions (115). The authors observed that their recorded spectra from an FPA were of poorer quality (lower SNR) than those recorded using a point-mapping approach through an aperture of 30 µm.…”
Section: Breast Tissuementioning
confidence: 99%